2012
DOI: 10.1139/p2012-048
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence for relativistic hadron emission from 32S nuclear collisions

Abstract: In this experiment, 32S interaction with emulsion nuclei is examined at 3.7A and 200A GeV. Backward relativistic hadron production seems to be an exact decay system, depending on the target size. For emulsion nuclei, the decay constant of this system nearly equals 1.3. Independent of the projectile size and energy, the backward relativistic hadrons are produced with probability values of ∼20%–30%. For projectile nuclei with mass numbers greater than or equal to 6 and at any incident energy, the average multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This strong dependence is evaluated linearly using equation ( 4) and is presented in figure 3 by the straight lines. Irrespective of the projectile size (A Proj = 1 to 32) and energy (2.1 to 200A GeV), the backward relativistic hadrons are produced with probability values of ∼20% to 30% for interactions with the Em target [36]. The theoretical predictions of the FRITIOF model slightly overestimate the data.…”
Section: Backward Relativistic Particle Productionmentioning
confidence: 93%
See 2 more Smart Citations
“…This strong dependence is evaluated linearly using equation ( 4) and is presented in figure 3 by the straight lines. Irrespective of the projectile size (A Proj = 1 to 32) and energy (2.1 to 200A GeV), the backward relativistic hadrons are produced with probability values of ∼20% to 30% for interactions with the Em target [36]. The theoretical predictions of the FRITIOF model slightly overestimate the data.…”
Section: Backward Relativistic Particle Productionmentioning
confidence: 93%
“…In experiments [18,19] the central collisions of 12 C, 16 O, 36 Ar, and 84 Kr with emulsion nuclei were studied at 50 to 220A MeV. At this range of intermediate energies the chance of pion creation is low.…”
Section: Mass Dependence Of the Collision Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In Experiment [47], 32 S collisions with emulsion nuclei, at two widely separated beam energies of 3.7A and 200 A GeV are studied to examine the behavior towards hadronization process. In Experiment [48], the same interactions are utilized to examine the target size dependence in the production of the forward and backward emitted relativistic hadrons in the framework of the Lund Monte-Carlo program code-events generating FRITIOF model [49][50][51].…”
Section: Commentmentioning
confidence: 99%
“…El-Nadi et al [5][6][7] showed that the backward emitted pion multiplicity is strongly correlated with the target fragment multiplicity at Dubna energy. The pion production was investigated in relativistic and ultrarelativistic collisions, underlying their zonal emission influence at, θ lab <90 • , forward hemisphere (FHS) [8][9][10][11][12]. These results suggested that the forward emitted pions originate from a source of particle creation system as a result of a fireball nuclear matter or hadronic matter decay.…”
Section: Introductionmentioning
confidence: 99%